Effect of Fe3O4 substrate preparation method for Fe3O4/Ag composite on methyl orange and 4-nitrophenol catalytic reduction - An Nang Vu; Ngoc – Hoa T. Le; Thanh- My T. Nguyen; Uyen N. Nguyen-Thai; Kim – Phung L. Nguyen; Lan Duc Vu (Desalination and Water Treatment)
We present a straightforward method for creating reusable magnetic Fe3O4/Ag catalysts. Three distinct Fe3O4 varieties were synthesized using different methods, and Ag nanoparticles were deposited onto the Fe3O4 matrix via a hydrothermal process. The resulting Fe3O4 and Fe3O4/Ag materials were characterized by XRD, XPS, FT-IR, Raman, DLS, FE-SEM, TEM, EDX, VSM, and UV-Vis spectroscopy. XRD analysis of the Fe3O4 particles synthesized using the solvothermal reduction process (S2) revealed firm diffraction peaks, indicating high crystallinity. After hydrothermal treatment, S2/Ag retained a hollow spherical morphology and magnetic properties similar to Fe3O4. The synthesized Fe3O4/Ag catalytic performance was evaluated for the reduction of 4-nitrophenol (4-NP) and methyl orange (MO) dye in the presence of NaBH4. All catalysts effectively reduced both dyes and could be magnetically separated from the aqueous solution. The P1/Ag catalyst achieved over 95 % reduction of MO and 4-NP within 2 minutes. S2/Ag exhibited superior stability, preventing Ag leaching during the reaction. Furthermore, its high saturation magnetization allows easy magnetic extraction from the solution. These findings strongly suggest S2/Ag as a promising catalyst due to its selectivity and advantageous properties.